The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5254/rct.19.81505
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological Elastomer Composites Based on Industrial Waste Nickel Zinc Ferrite and Natural Rubber

Abstract: Magnetorheological elastomers (MREs) based on waste nickel zinc ferrite and natural rubber were prepared. The amount of waste nickel zinc ferrite was varied at five levels (20, 40, 60, 80, and 100 phr) to assess the optimum amount of waste nickel zinc ferrite content for highest dynamic mechanical and tensile performance. Curing characteristics of the MREs were determined by moving disk rheometer (MDR 2000), and thermal properties were evaluated by thermogravimetric analysis (TGA). Tan δ was measured through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…The efficiency of different silane treatment methods on the elongation at the break of the rubber composites is shown in Figure 5(b). The elongation at break of unfilled natural rubber was approximately 300% as reported in our previous work 61 . As expected, the elongation at break for rubber composites with treated fillers is lower compared to those with untreated fillers.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The efficiency of different silane treatment methods on the elongation at the break of the rubber composites is shown in Figure 5(b). The elongation at break of unfilled natural rubber was approximately 300% as reported in our previous work 61 . As expected, the elongation at break for rubber composites with treated fillers is lower compared to those with untreated fillers.…”
Section: Resultssupporting
confidence: 87%
“…Figure 4(a) shows the effects of different silane treatment methods on the tensile strength of elastomeric composites containing silica, ferrite and kenaf fiber. The tensile strength of unfilled natural rubber was approximately 2.5 MPa as reported in our previous work 61 . Comparison of tensile strength for untreated fillers filled natural rubber revealed that introducing untreated silica to natural rubber increased the tensile strength to 12.5 MPa, for untreated ferrite particles filled natural rubber the tensile strength increased to 8 MPa, and for untreated kenaf filled natural rubber, the tensile strength increased to 4.6 MPa.…”
Section: Resultssupporting
confidence: 82%
“…This means that Ni-Mg cobalt ferrite nanoparticles increase the interaction between MRE and particles. On the other hand, Nordalila et al [ 64 ] manufactured MRE using industrial waste nickel-zinc ferrite. Experiments were conducted to compare the degree of swelling according to the content of nickel-zinc ferrite.…”
Section: Mre Materialsmentioning
confidence: 99%
“…The large size CIPs of 6.25-µm diameter exhibit fairly uniform distribution, whereas small diameter CIPs produce agglomerates in the matrix. In the case of small diameter CIPs, the distance between particles was observed to be smaller and filler–filler particle interactions was greater, resulting in agglomeration of particles [ 99 ]. The addition of 10 wt% silicone oil causes more homogeneous dispersion of CIPs in the SR matrix without any structuring or surface defect [ 29 ].…”
Section: Properties Of Isotropic Magnetorheological Elastomersmentioning
confidence: 99%
“…With the increase of volume fractions of particles, the distance between the particles decreases and results in poor dispersion, greater agglomeration, and poor properties. This might also be attributed to the greater filler–filler particle interaction and lower filler–matrix interaction at a higher volume fraction of magnetic filler particles [ 99 ]. In the fabrication of isotropic MREs, homogenous dispersion of filler particles is usually achieved by the use of appropriate additives, such as slackers or silicon thinner, or by ultrasonication for sufficient time.…”
Section: Properties Of Isotropic Magnetorheological Elastomersmentioning
confidence: 99%